Evaluation of influenza vaccination coverage in Shanghai city during the 2016/17 to 2020/21 influenza seasons. Issue 5 (30th November 2022) - Wu, Linlin; Guo, Xiang; Liu, Jiechen; Ma, Xiaoying; Huang, Zhuoying; Sun, Xiaodong
ABSTRACT: Influenza is a common infectious disease resulting in substantial morbidity and mortality globally. The most effective strategy for preventing influenza is annual vaccination; however, the coverage rate of the influenza vaccine in Shanghai has not been well explored or reported. Therefore, this study aimed to determine coverage with the influenza vaccine and access trends in Shanghai city; data from Shanghai immunization information system was analyzed to estimate vaccination coverage during 2016–2017 through 2020–2021 influenza seasons. Vaccination coverage by age groups, immigration status, and districts was accessed. The influenza vaccination coverage (at least one dose) for 2016/2017 to 2020/2021 influenza seasons was 10.8‰ (95‰ CI: 10.7–10.8), 12.3‰ (95‰ CI: 12.3–12.4), 10.1‰ (95‰ CI: 10.0–10.1), 20.1‰ (95‰ CI: 20.0–20.2) and 50.8‰ (95‰ CI: 50.7–50.8) respectively. Although we found significantly higher vaccination coverage in females, children from 6 months to 17 years, and residents, it is still low in all subgroups of the population in Shanghai. Therefore, taking effective steps to promote influenza vaccination in Shanghai is recommended.